Metal 3D printing via selective laser melting and direct metal deposition: materials, properties and applications - Wang, Jing Jing (2016)
Recently, metal 3D printing has gained a lot of interest. In particular, selective laser melting (SLM) and direct metal deposition (DMD) are the most important methods explored due to the superior properties being achieved. This article overviews the two methods in terms of basics of the technologies (powder bed fusion and powder blow), material selection, properties as well as some of the applications and future directions. SLM is superior in producing parts with higher precision and complexity. However, DMD is more processing efficient and allows for large components to be manufactured. A recent design of hybrid system of DMD with milling technology can achieve high precision and surface finishing. Moreover, DMD can also produce functionally graded materials (FDMs) as well as composite materials.